Biomarkers of Checkpoint Inhibitor Induced Immune-Related Adverse Events—A Comprehensive Review - Hommes, Josefien W.; Verheijden, Rik J.; Suijkerbuijk, Karijn P. M.; Hamann, Dörte (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICIs) have substantially improved the prognosis of patients with different types of cancer. Through blockade of cytotoxic T-lymphocyte antigen 4 (CTLA-4) and programmed cell death protein 1 (PD-1), negative feedback mechanisms of the immune system are inhibited, potentially resulting in very durable anti-tumor responses. Despite their promise, ICIs can also elicit auto-immune toxicities. These immune-related adverse events (irAEs) can be severe and sometimes even fatal. Therefore, being able to predict severe irAEs in patients would be of added value in clinical decision making. A search was performed using ‘adverse events’, ‘immune checkpoint inhibitor’, ‘biomarker’ and synonyms in PubMed, yielding 3580 search results. After screening title and abstract on the relevance to the review question, statistical significance of reported potential biomarkers, and evaluation of the remaining full papers, 35 articles were included. Five additional reports were obtained by means of citations and by using the similar article function on PubMed. The current knowledge is presented in comprehensive tables summarizing blood-based, immunogenetic and microbial biomarkers predicting irAEs prior to and during ICI therapy. Until now no single biomarker has proven to be sufficiently predictive for irAE development. Recommendations for further research on this topic are presented.